More answers

x2 = 92 - 2x2

x2 + 2x2 = 92

3x2 = 81

x2 = 81/3

x2 = 27

x = 5.196 (to 3 decimal places only)

Q: What is x squared equals 9 squared - 2x squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Yes it is. The thing that makes it a quadratic equation is that "x squared" in there.

x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0

2x + 52 = 7 2x + 25 = 7 2x = 7 - 25 2x = -18 x = -18/2 x = -9

Yes it is and well done.

(2x - 7)(5x + 9) ie x = 3.5 or -1.8

Related questions

Yes it is. The thing that makes it a quadratic equation is that "x squared" in there.

x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0

2x + 52 = 7 2x + 25 = 7 2x = 7 - 25 2x = -18 x = -18/2 x = -9

Yes it is and well done.

No, x + x equals 2x. x times x equals x2. (x times x equals x squared.)

(2x - 7)(5x + 9) ie x = 3.5 or -1.8

48

2x = -x +9

It is an algebraic expression involving x. Of do you mean 'what is x if 2x - 9 equals 9?' 2x - 9 = 9 ⇒ 2x - 9 + 9 = 9 + 9 ⇒ 2x = 18 ⇒ 2x ÷ 2 = 18 ÷ 2 ⇒ x = 9

6

If 5 x equals 9 plus 2x then x equals?

2 x cosine squared x -1 which also equals cos (2x)